Correlation of Papillomacular Nerve Fiber Bundle Thickness with Central Visual Function in Open-Angle Glaucoma - Wataru Kobayashi; Hiroshi Kunikata; Kazuko Omodaka; Kyousuke Togashi; Morin Ryu; Masahiro Akiba; Gaku Takeuchi; Tetsuya Yuasa; Toru Nakazawa (Journal of Ophthalmology)
Purpose. To determine the correlation of reduced retinal thickness in the central papillomacular bundle (CPB) to central visual function, including central retinal sensitivity and visual acuity, in glaucoma patients. Methods. This study enrolled 50 eyes of 50 patients with open-angle glaucoma who were carefully screened for comorbid conditions that can cause decreased central visual function, such as cataracts or macular diseases. We used a novel CPB analysis comprising a program for optical coherence tomography that measured RNFL thickness and GCC thickness in the CPB and divided lengthwise into three parts (upper, middle, and lower CPB). The relationship of these parameters, including conventional macular thickness, to visual field sensitivity in four central standard automated perimetry points (the central four thresholds) and BCVA was analyzed. Results. The two parameters most highly correlated with central four thresholds were macular GCCT and macular RNFLT. The two parameters most highly correlated with BCVA were middle CPB (mid-CPB) GCCT and mid-CPB RNFLT. A multiple regression analysis revealed that mid-CPB GCCT was an independent factor impacting central retinal thresholds and BCVA. Conclusions. Our results suggest that mid-CPB RNFLT and GCCT, parameters of a novel papillomacular bundle analysis, are candidate biomarkers of decreased central visual function in glaucomatous eyes.